Nuruosmaniye Kütüphanesi No: 4967’de kayıtlı Mecmūʿa-İ Eş’ar (Vr. 1b-80a) : (inceleme – tenkitli metin) - Delican, Merve (My University, 2014)
Çalışmamız, Nuruosmaniye Kütüphanesi 4967 numarada kayıtlı şiir mecmuasının 1b-80a varaklarının transkripsiyonlu metninden ve bu metnin incelenmesinden oluşmaktadır. Çalışmada öncelikle mecmualar hakkında genel bilgi verilmiş daha sonra çalışmamıza konu olan şiir mecmuasının muhtevası tarafımızdan incelenmiştir. 1b-80a varaklarının transkripsiyonlu metni basılmış divanlarla karşılaştırılarak oluşturulmuş, farklılıklar ve açıklamalar dipnotlarda belirtilmiştir. Mecmuanın istinsah tarihi tespit edilememiştir. Mecmua kütüphane kayıtlarına toplamda 166 varak olarak kaydedilmiştir fakat mecmuanın toplam varak sayısı155’tir. Mecmuada ağırlıklı olarak 17. yüzyıl şairlerinin şiirleri yer almaktadır. Mecmuanın tümünde 86 şair tespit edilmiştir. Çalışmamıza ait kısımda toplam 326 şiir bulunmaktadır. Bu şiirlerin 121 tanesi Tecelli’ye aittir.

Our study comprises of the transcripted passage and its analysis on pages of 1b-80a in the collection of poems numbered 4967 in the Nuruosmaniye library. We give a brief introduction about the collection followed by our detailed analysis about its contents. This text was formed by comparing the transcripted folio 1b-80a with printed divans.The differences and explanations are indicated in the footnotes. Date of the copy of the collection could not be determined. According to the register of the Nuruosmaniye Library this poem collection consists of 166 pages, however, the eventual copy consists of 155 folios. In this poem collection, 17 century poets were mainly featured. 86 poets were identified in the whole collection. Our analysis contains 326 poems, 121 of these belong to Tecelli. ABSTRACT Our study comprises of the transcripted passage and its analysis on pages of 1b-80a in the collection of poems numbered 4967 in the Nuruosmaniye library. We give a brief introduction about the collection followed by our detailed analysis about its contents. This text was formed by comparing the transcripted folio 1b-80a with printed divans.The differences and explanations are indicated in the footnotes. Date of the copy of the collection could not be determined. According to the register of the Nuruosmaniye Library this poem collection consists of 166 pages, however, the eventual copy consists of 155 folios. In this poem collection, 17 century poets were mainly featured. 86 poets were identified in the whole collection. Our analysis contains 326 poems, 121 of these belong to Tecelli. ABSTRACT Our study comprises of the transcripted passage and its analysis on pages of 1b-80a in the collection of poems numbered 4967 in the Nuruosmaniye library. We give a brief introduction about the collection followed by our detailed analysis about its contents. This text was formed by comparing the transcripted folio 1b-80a with printed divans.The differences and explanations are indicated in the footnotes. Date of the copy of the collection could not be determined. According to the register of the Nuruosmaniye Library this poem collection consists of 166 pages, however, the eventual copy consists of 155 folios. In this poem collection, 17 century poets were mainly featured. 86 poets were identified in the whole collection. Our analysis contains 326 poems, 121 of these belong to Tecelli.
Keywords: Tarih ve Eleştiri; Türk Edebiyatı